1997
DOI: 10.1073/pnas.94.21.11156
|View full text |Cite
|
Sign up to set email alerts
|

An artificial cytochrome P450 that hydroxylates unactivated carbons with regio- and stereoselectivity and useful catalytic turnovers

Abstract: A catalyst has been synthesized comprising a manganese porphyrin carrying four beta-cyclodextrin groups. It catalyzes the hydroxylation of substrates of appropriate size carrying tert-butylphenyl groups that can hydrophobically bind into the cyclodextrin cavities. In one example as many as 650 catalytic turnovers are seen before the catalyst is oxidatively destroyed, and with a rate comparable to that of typical cytochrome P450 enzymes. In another example, a steroid derivative is regio-and stereoselectively hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 21 publications
0
70
0
Order By: Relevance
“…[35][36][37][38] An artificial enzyme system which perfectly illustrates the possibility to achieve high selectivity is the manganese porphyrin 7, which possesses four covalently linked peripheral -CDs (Figure 1c). [39][40][41][42][43] In the presence of iodosyl benzene, this tetramer is capable of selectively epoxidizing or hydroxylating stilbene derivatives. Its superior selectivity is best illustrated by the fact that it can regio-and stereoselectively oxidize the unactivated 6-CH 2 position in the B-ring of steroid derivative 8.…”
Section: Covalent Systemsmentioning
confidence: 99%
“…[35][36][37][38] An artificial enzyme system which perfectly illustrates the possibility to achieve high selectivity is the manganese porphyrin 7, which possesses four covalently linked peripheral -CDs (Figure 1c). [39][40][41][42][43] In the presence of iodosyl benzene, this tetramer is capable of selectively epoxidizing or hydroxylating stilbene derivatives. Its superior selectivity is best illustrated by the fact that it can regio-and stereoselectively oxidize the unactivated 6-CH 2 position in the B-ring of steroid derivative 8.…”
Section: Covalent Systemsmentioning
confidence: 99%
“…When we attached two or four cyclodextrins to a porphyrin, we were able to use the iron derivative or even better the manganese derivative to carry out directed hydroxylations of unactivated carbon-hydrogen bonds in a bound steroid using the binding of the steroid into the cyclodextrin units [23][24][25][26]. With binding into two cyclodextrins on opposite sides of the porphyrin we saw selective hydroxylation at C-6 in a cholestanol derivative, while with triple binding into three cyclodextrins we selectively hydroxylated C-9, giving an entry into corticosteroids.…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…In the natural P-450 enzymes the iron porphyrin is axially coordinated by a cysteine thiolate sulfur and the oxygen adds to the sixth coordination position. Initially, imidazole had been incorporated as the fifth ligand in such P450 mimics [180,414,415,418]. Inclusion of thiolates in the P450 mimic either covalently attached (see 665) or via hydrogen bounding to the catalyst allowed the use of H 2 O 2 as oxidant [419] .…”
Section: Catalysismentioning
confidence: 99%
“…These compounds display significant inhibitory effects and offer potential for the treatment of herpes virus infections [30] . Another broad study compared the antiviral effect of neutral porphyrins (412,414,415) and their cationic analogues (416a-c) against HSV-1 [229] . With the exception of 416a all compounds gave IC 50 Earlier it had been shown that the fully deprotected derivative have the best activity [30] .…”
Section: Antiviral and Antifungal Pdtmentioning
confidence: 99%
See 1 more Smart Citation